2006
DOI: 10.2298/jsc0609985b
|View full text |Cite
|
Sign up to set email alerts
|

The influence of microstructural characteristics on the mechanical properties of Ti6Al4V alloy produced by the powder metallurgy technique

Abstract: The influence of hot-pressing (HP-ing) parameters on the microstructure tensile properties and impact toughness of Ti6Al4V alloy produced by the powder metallurgy (PM) technique was evaluated. The experimental results show that variations in the microstructural morphology and residual porosity play an important role in affecting the mechanical properties of this alloy. The lamellar microstructure with a higher density, obtained by HP-ing above the ?-transition temperature (T?), was found to exibit a higher ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…61 Saffar et al 62 demonstrated that elongation at break decrease with crystalline orientation. Also, Bozic et al 63 showed that substrates with coarse lamellar structures possessed higher elongation compared to those with ne lamellar microstructures.…”
Section: Afm Analysismentioning
confidence: 99%
“…61 Saffar et al 62 demonstrated that elongation at break decrease with crystalline orientation. Also, Bozic et al 63 showed that substrates with coarse lamellar structures possessed higher elongation compared to those with ne lamellar microstructures.…”
Section: Afm Analysismentioning
confidence: 99%
“…Furthermore, it has been shown that following the processing by the HP technique, the porosity of the samples is residual and thus close to fully densified specimens were obtained. 31,32 After this procedure, the samples were polished in order to adequate the contact surfaces for tribological testing. A progressive polishing with silicon carbide abrasive papers from 120 to 3000 grit sizes were used for all samples, resulting in a final average surface roughness R a 5 0.48 6 0.05 mm.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated in another study, under submission, that the addition of a bioactive phase to the Ti alloy substantially increases its bioactivity. Furthermore, it has been shown that following the processing by the HP technique, the porosity of the samples is residual and thus close to fully densified specimens were obtained . After this procedure, the samples were polished in order to adequate the contact surfaces for tribological testing.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its relatively low density compared to other structural materials, titanium can be classified as a lightweight material. These properties, along with its good biocompatibility, make titanium a great choice for biomedical applications [ 1 , 2 ]. Nowadays, a lot of Ti alloys can be found, among them, the most used for orthopedic applications is the Ti-6Al-4V alloy, due to its low density, resistance to corrosion and relatively low stiffness [ 3 ].…”
Section: Introductionmentioning
confidence: 99%